Translation strategies for metaphors in Fortress Besieged from Chinese into English based on semantic and communicative translation - Tian, Dandan (2024)
The Fortress Besieged is a contemporary satire that is often referred to as an “encyclopaedia of metaphors” in Chinese literature. In satirical works, these metaphors often carry multi-layered meanings, and these cultural differences are magnified, making translation even more difficult. The loss of metaphorical imagery not only means the loss of the cultural connotations and satirical impact of the original work, but also causes readers to misunderstand the true meaning of the source text, which is unacceptable. Therefore, this study focuses on the translation strategies of metaphors in Fortress Besieged and aims to: (1) identify translation strategies that translators employ when translating metaphors from Chinese into English in Fortress Besieged; (2) analyse the outcomes that such translation strategies produce in terms of preserving the metaphorical images and meanings; and (3) discuss the reduction of these inappropriate outcomes arising from the metaphor translation strategies used in Fortress Besieged, based on the combination of Newmark’s semantic and communicative translation. Drawing on Newmark’s (1981) semantic and communicative theories, which outline the preservation of metaphorical images and the communication of metaphorical meaning, this study applies a qualitative interpretive paradigm to analyse the metaphor translation strategies employed by the American translator and writer Jeanne Kelly and the Chinese-American scholar Nathan K. Mao. The analysis of the translation strategies for 261 metaphors in Fortress Besieged revealed that 52.9% of the metaphorical images were omitted in the English translation because there were no English equivalents or because the communicative translation strategy was only to convey the intended meaning. The study found that 68.6% of the metaphor translations produced appropriate outcomes (either preserving both image and meaning or meaning alone). 31.4% of the translations resulted in inappropriate outcomes (losing either image, meaning, or both). The study highlighted that cultural and linguistic gaps led to the loss of the metaphorical images in more than half of the translations, diminishing cultural connotations and literary values. In this study, Newmark’s (1981) metaphor translation procedures were adapted to better accommodate the translation of metaphors with the particular cultural background of China. Based on the combination of semantic and communicative translation strategy, the study aims to achieve a more accessible translation through the appropriate use of translation strategies in order to preserve the metaphorical images while explaining the metaphorical meaning to reflect the emotional nuances and literary value of the source text. Therefore, exploring the translation of metaphors in satirical novels such as Fortress Besieged is crucial as it helps to reproduce the linguistic artistry and aesthetic value of literary works.